Impact of COVID-19 specific simulation training in improving intubators' level of comfort during intubations of COVID-19 patients - Results from a USA national survey. (April 2022) - Al Shabeeb, Reem Qabas; Lee, Esther; El Shatanofy, Muhammad; Mulcahy, Collin F.; Sherman, Marian L.; Heinz, Eric R.; Yamane, David P.
Abstract: Background: Tracheal intubation is a hazardous aerosolizing procedure with a potential risk of spreading SAR-CoV-2 between patients and physicians. Aim: The purpose of this study was to explore the impact of COVID-19 specific simulation training in improving provider level of comfort during the intubation of COVID-19 patients. Methods: In this cross-sectional national study, an electronic survey was disseminated using a snowball sample approach to intubators from 55 hospitals across the United States. The survey assessed providers' comfort of intubating and fear of contracting the virus during COVID-19 intubations. Results: A total of 329 surveys from 55 hospitals were analyzed. Of 329 providers, 111 providers (33.7%) reported participating in simulation training. Of those, 86 (77.5%) reported that the simulation training helped reduce their fear of intubating COVID-19 patients. Providers in the simulation training group also reported a higher level of comfort level with intubating both general patients (median [range] no-simulation training group 9 [3–10], simulation training group 9 [6–10]; p = 0.015) and COVID-19 patients (no-ST 8 [1–10], ST group 9 [4–10]; p < 0.0005) than providers in the no-simulation training group. Conclusions: Our study suggests that COVID-19 specific intubation simulation training promotes provider comfort. Simulation training may be implemented as part of airway management training during the current and novel pandemic situations. Highlights: Simulation training in airway management improves technical and non-technical skills in high-risk clinical scenarios. COVID-19 specific intubation simulation training may improve providers' comfort and fear levels during intubations. Future research should compare how different simulation exercises affect providers' comfort and fear levels.